Complete chloroplast genome of medicinal plant Aconitum carmichaelii: genome characterization and phylogenetic analysis. Issue 1 (1st January 2016) - Gao, Jihai; Zhang, Dayan; Wang, Wei; Peng, Cheng
Abstract: The complete chloroplast genome sequence of an important medicinal plant of the family Ranunculaceae, Aconitum carmichaelii Debx., was characterized in this study. The assembled chloroplast genome was 154, 776 bp in length, which included a large single-copy (LSC), a small single-copy (SSC), and two inverted repeat (IR) regions of 86, 330bp, 15, 986 bp, and 26, 193 bp, respectively. The GC content of the genome was 38.1%. Phylogenetic analysis with the whole nucleotide sequences of reported Aconitum chloroplast genomes indicated a close relationship of A. carmichaelii with A. kusnezoffii .